2003
DOI: 10.1038/ng1241
|View full text |Cite
|
Sign up to set email alerts
|

A novel ubiquitin ligase is deficient in Fanconi anemia

Abstract: Fanconi anemia is a recessively inherited disease characterized by congenital defects, bone marrow failure and cancer susceptibility. Cells from individuals with Fanconi anemia are highly sensitive to DNA-crosslinking drugs, such as mitomycin C (MMC). Fanconi anemia proteins function in a DNA damage response pathway involving breast cancer susceptibility gene products, BRCA1 and BRCA2 (refs. 1,2). A key step in this pathway is monoubiquitination of FANCD2, resulting in the redistribution of FANCD2 to nuclear f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
562
0
6

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 533 publications
(581 citation statements)
references
References 29 publications
11
562
0
6
Order By: Relevance
“…In the case of FancD2, carboplatin led to the appearance of a second protein species with higher molecular weight ('FancD2-L'; Figure 6a), corresponding to monoubiquitinated FancD2 that is induced by the upstream components of the pathway upon activation. 31 When carboplatin was combined with ganetespib, FancD2 was not only reduced in its total levels, but the upper band corresponding to ubiquitinated FancD2 disappeared completely. Thus, both the key components and key functionality of the FA pathway are compromised by HSP90 inhibition.…”
Section: Carbomentioning
confidence: 93%
“…In the case of FancD2, carboplatin led to the appearance of a second protein species with higher molecular weight ('FancD2-L'; Figure 6a), corresponding to monoubiquitinated FancD2 that is induced by the upstream components of the pathway upon activation. 31 When carboplatin was combined with ganetespib, FancD2 was not only reduced in its total levels, but the upper band corresponding to ubiquitinated FancD2 disappeared completely. Thus, both the key components and key functionality of the FA pathway are compromised by HSP90 inhibition.…”
Section: Carbomentioning
confidence: 93%
“…2d), suggesting that RAD18 is not the E3 ligase for USP1 degradation. Previous studies have indicated that the UV-dependent monoubiquitination of FANCD2 requires an intact Fanconi anaemia core complex 20,21 -a multisubunit E3 ligase containing at least eight Fanconi anaemia protein subunits (A, B, C, E, F, G, L and M) 22,23 . The Fanconi anaemia core complex was systematically excluded from the degradation of USP1, as analysis of patient-derived Fanconi anaemia fibroblasts from different Fanconi anaemia subtypes (FA-A, FA-C, FA-G and FA-L) showed that they remained competent for USP1 degradation and for the monoubiquitination of PCNA (Fig.…”
Section: Uv Damage Degrades Usp1 and Increases Pcna Monoubiquitinationmentioning
confidence: 99%
“…We showed that FAAP43 (also called FANCL) is a ubiquitin ligase and was defective in an individual affected with Fanconi anemia belonging to a new complementation group (FA-L) 3,7 (Fig. 1a).…”
mentioning
confidence: 99%